1997
DOI: 10.1136/thx.52.10.929
|View full text |Cite
|
Sign up to set email alerts
|

Markers of inflammation in induced sputum in acute bronchitis caused by Chlamydia pneumoniae.

Abstract: Little is known of the inflammatory characteristics of acute infections of the respiratory tract caused by virus and unusual bacteria such as Chlamydia pneumoniae. A case is reported in whom inflammatory indices in sputum were used to investigate, for the first time, the airway inflammation during an episode of acute bronchitis caused by C pneumoniae. The patient presented with a dry cough of five days duration. C pneumoniae was identified by polymerase chain reaction (PCR) in a nasopharyngeal swab collected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…There is limited data on the normal host immune response to C. pneumoniae. A case report of an acute infection in asthma found an acute lymphocytic infiltrate [3]. Infection with C. trachomatis results in an acute neutrophilic infiltrate followed by an increase in plasma cell numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited data on the normal host immune response to C. pneumoniae. A case report of an acute infection in asthma found an acute lymphocytic infiltrate [3]. Infection with C. trachomatis results in an acute neutrophilic infiltrate followed by an increase in plasma cell numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Acute C. pneumoniae infection can cause exacerbation of asthma [3], and chronic/persistent infection has been linked to chronic persistent asthma, and adult onset asthma [4]. Children with increased levels of secretory immunoglobulin (Ig) A directed against C. pneumoniae were found to have more frequent clinical exacerbations of asthma [5], whereas, in adults with asthma, higher titres of antibodies directed against C. pneumoniae were associated with more severe clinical disease [6,7].…”
mentioning
confidence: 99%
“…Eosinophilic inflammation is caused by allergens (187)(188)(189), occupational chemical sensitizers (190,191), and reduction of steroid in steroid-dependent asthma (192). In contrast, noneosinophilic inflammation is caused by cigarette smoking (193,194), different types of infection (including viral) (185,195), endotoxin (196), and ozone (197) and occurs in steroid-resistant asthma (179).…”
Section: Inflammatory Markers In Asthmamentioning
confidence: 99%
“…This rapid fall in levels of sputum chemoattractants and inflammatory markers following treatment has been also reported in patients with COPD and ␣-1-antitrypsin deficiency (31). This type of inflammatory response is not limited to COPD exacerbations caused by common bacteria, because similar findings have been reported with bronchial infections due to Chlamydia pneumoniae (32 Neutrophils are not the only inflammatory cell that seem to have an important role in COPD. Balzano and colleagues (33) studied bronchial secretions obtained through sputum induction in patients with COPD, asthma, asymptomatic smokers, and healthy nonsmokers, and found that during stable periods, neutrophils were significantly higher in COPD patients than in the other groups, but also eosinophils were increased in patients with COPD when compared to healthy controls.…”
Section: The Inflammatory Response To Bronchial Colonizationmentioning
confidence: 56%